2009
DOI: 10.1007/s10725-009-9380-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of salicylic acid and salinity on some antioxidant activities, oxidative stress and metabolite accumulation in Phaseolus vulgaris

Abstract: It has been shown that salicylic acid (SA) acts as an endogenous signal molecule responsible for inducing abiotic stress tolerance in plants. The effect of SA and sodium chloride (NaCl) on growth, metabolite accumulation, oxidative stress and enzymatic and non-enzymatic antioxidant responses on common bean plants (Phaseolus vulgaris, cv. F-15) was studied. Results revealed that either SA or NaCl decrease, shoot, root and total plant dry weights. SA treatments decreased the contents of proline, and reduced form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 41 publications
2
24
0
2
Order By: Relevance
“…Moreover, the increased GSH content maintains the proper functioning of enzymes of ascorbate-glutathione pathway, and results in the increased activity of GR and APX with the application of 0.5 mM SA under salt stress. The increase in antioxidant enzymes with SA has been reported by , Wang and Li (2006), Palma et al (2009) and Syeed et al (2010) under different stress conditions. The activity of APX and GR and the GSH content were inhibited by 1.0 mM SA application leading to maximum production of H 2 O 2 , TBARS and electrolyte leakage.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, the increased GSH content maintains the proper functioning of enzymes of ascorbate-glutathione pathway, and results in the increased activity of GR and APX with the application of 0.5 mM SA under salt stress. The increase in antioxidant enzymes with SA has been reported by , Wang and Li (2006), Palma et al (2009) and Syeed et al (2010) under different stress conditions. The activity of APX and GR and the GSH content were inhibited by 1.0 mM SA application leading to maximum production of H 2 O 2 , TBARS and electrolyte leakage.…”
Section: Discussionmentioning
confidence: 84%
“…The results suggested that the level of oxidative stress correlated with the contents of non-enzymatic antioxidants, which may contribute to the tolerance of C. album to 300 mM NaCl stress. It was also found that the AsA content in leaves of C. album was about 30-fold compared to that in Phaseolus vulgaris (Palma et al 2009). Such high levels of non-enzymatic antioxidants in C. album may endow this species with a strong ability to resist potential oxidative damage.…”
Section: Discussionmentioning
confidence: 92%
“…Salt stress is known to: impair the cellular electron transport within the different subcellular compartments (Ashraf 2009); reduce gas exchange thereby limiting CO 2 supply to the leaf (Asada 1999) and cause over-reduction of the photosynthetic electron transport chain (Asencio et al 2003) and thereby the over-production of ROS (Asada 1999;Asencio et al 2003;Foyer and Noctor 2009). To acclimate to adversity, plants can detoxify ROS by producing different types of antioxidants (Foyer and Noctor 2005;Palma et al 2009). Intracellular levels of ROS in plant depend on their rates of generation, their rate of reaction with other metabolites, their rate of degradation, and rate of their scavenging by enzymatic and/or non-enzymatic antioxidants (Mittler 2002;Amor et al 2005;Foyer and Noctor 2005).…”
Section: Discussionmentioning
confidence: 99%